(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
The present study examines the leaf variations in leaf traits of four Hoya R. Br. species from Philippines namely: (1) H. buotii Kloppenburg, (2) H. halconensis Kloppenburg, (3) H. mindorensis Schlechter red bearing flowers; and (4) H. mindorensis Schlechter yellow bearing flowers. Leaf samples (n= 30 leaves) were collected from each plant group and measured with nine architectural traits. The results showed variability in the leaves using univariate and multivariate analysis. Data ordination depicted variations in leaf morphology. The two plant groups H. mindorensis red bearing flowers and H. mindorensis yellow bearing flowers were consistently variable as supported by principal coordinate analysis, cluster analysis and two way Anova (P<0.001). The variability of the two plant groups could be due to developmental instability, plasticity or taxonomic identity, one being the subspecies of the other. Hence, a closer study to investigate the significant variability of the two plant groups was recommended. Distinct separation of H. buotii and H. halconensis was detected being regularly mistaken as one species. The study demonstrated the applicability of multivariate analysis as effective tool in numerical taxonomy. Multivariate analysis can be employed to demonstrate likelihood of relationship among various Hoya species. Bangladesh J. Plant Taxon. 23(2): 199-207, 2016 (December)